Use of telephone intake for family history taking at a cancer genetics service in Asia. Issue 6 (5th May 2020) - Chin, Xin Wei; Ang, Zoe L. T.; Tan, Ryan Y. C.; Courtney, Eliza; Shaw, Tarryn; Chen, Yanni; Li, Shao‐Tzu; Ngeow, Joanne Yuen Yie
Abstract: Family history taking is a fundamental part of genetic counseling, and however, it is also a time‐consuming process. To cope with the increasing demands at the Cancer Genetics Service in Singapore, alternative methods to collect patients' family history were implemented to reduce the duration of the initial consultation and increase the clinic's capacity. Two interventions were performed in this study, where a family history questionnaire and telephone intakes (telephone calls to collect patient family history) were implemented prior to a cancer genetics consultation. The primary outcome of this study is the duration of the initial consultation in relation to both interventions while the secondary outcome is the clinic attendance rate before and after implementing the telephone intake. The impact of interventions was evaluated with a Plan‐Do‐Study‐Act (PDSA) methodology. The use of a family history questionnaire could not be evaluated due to poor patient response while the telephone intake was found to be feasible among the local population. Two improvements were observed after the implementation of telephone intake: (a) a significant reduction in the duration of the initial consultation from 60 to 45 min ( p  = .001) and (b) a significant increase of 29.7% in clinic attendance ( p  = .01). This study demonstrates that collecting family history information ahead of genetic counseling via telephone intake is a useful measure in improving clinic capacity, which potentially resulting in optimization of clinical resources.